Border Sharing – a Quantitative Analysis of Contributions to FRONTEX 2012–2018. Issue 7 (3rd October 2021) - Baër, Sabine; Beeres, Robert; Bollen, Myriame
ABSTRACT: From 2011, due to war, conflict, and ensuing unrest, both in the Middle East and Africa, the European Union's southern external borders were confronted with an influx of migrants and refugees. At its height, the influx became known as a migration (or refugee) crisis and the European Border and Coast Guard Agency (FRONTEX) was perceived as a pivotal partner in crisis management at the borders. FRONTEX does not avail of its own operators nor materiel, and, consequently, Schengen member states and Schengen Associated Countries were requested to contribute personnel and equipment for operations. From 2012 to 2018, this article analyzes the member states' burden-sharing behavior regarding their contributions to European Border Guard Teams and Technical Equipment Pool. Our findings include both over- and under-contributors. As the sum total of contributions over all member states is high, it could be concluded, member states derive common benefits from border management. However, results also show that, as compared to others, member states situated at the European Union's Southern and Eastern borders, on average, are over-contributing. Moreover, contributions from individual member states fluctuate over time. Apparently, the acquired benefits are not always perceived in the same way.